The Influence of Parents Economic Level And Motivation On Mathematics Learning Outcomes - Sodikin, Sodikin (Universitas Wiralodra, 2023)
This research aims to determine the influence of parents' economic level and student motivation on mathematics learning outcomes in private vocational school students in Indramayu Regency. This research uses quantitative research methods with correlational survey research techniques. The analysis technique used in this research is path analysis. The population is all class X vocational school students in Indramayu Regency. The sample in the research was 50 students. The results of the research prove that there is an insignificant direct influence of the economic level of parents on mathematics learning outcomes which is proven to obtain a sig value of 0.078 > 0.05 with tobs 1.804, there is an insignificant direct influence of motivation on mathematics learning outcomes. with a sig value of 0.866 > 0.05 with a tobs of 1.70 and there is a significant direct influence on the economic level. parents' influence on motivation is proven by a sig value of 0.010 < 0.05 with a value of tobs 2.663 and there is an insignificant direct influence on economic level. parents on mathematics learning outcomes through. motivation as evidenced by tobs 0.498 < ttable. 1.677. The results of the research can be used as input to vocational school level teachers, especially mathematics teachers, to always motivate students and provide learning support so that they can optimize student learning outcomes.